Potential Drug-Drug Interaction (DDI) in Type 2 Diabetes Mellitus Outpatients in Palembang: a Retrospective Study - Sonlimar Mangunsong; Fadly Akbar; Mona Rahmi Rulianti; Vera Astuti; Lilis Maryanti; Sarmalina Simamora; Abdul Gani (Jurusan Farmasi Universitas Negeri Gorontalo, 2026)
This study aimed to identify and describe potential drug–drug interactions (DDIs) among outpatients with type 2 diabetes mellitus (T2DM) at Hospital X (Palembang, Indonesia) by analysing patient characteristics, patterns of antidiabetic drug use, comorbidities, concomitant medications, and the severity of potential interactions. A descriptive retrospective design was applied using secondary data from outpatient medical records during January–December 2024. From a total of 1,486 records, 316 eligible records were included based on predefined inclusion criteria, with the minimum sample size determined using Slovin’s formula. Potential DDI severity was categorised into major, moderate, and minor. Most patients were female (66.13%) and aged ≥60 years (51.58%). Metformin was the most frequently prescribed antidiabetic drug (25.38%), followed by insulin Apidra (15.45%), insulin Sansulin (14.12%), and glimepiride (12.78%). Potential DDIs were identified in 255 patients (80.69%); across 649 interaction events, most were moderate (93.52%), followed by minor (5.72%) and major (0.75%). The remaining 61 patients (19.31%) had no potential DDIs. Overall, the high utilisation of multi-drug regimens in outpatient T2DM care is associated with substantial exposure to potential DDIs, predominantly of moderate severity, underscoring the need for routine medication review and therapeutic monitoring to improve medication safety, with clinical pharmacists playing an important role in supporting prescribers.